Study on the level of acceptance of MyKad application among non academic staff in UiTM Jengka Pahang / Siti Azleah Hanim Jaafar, Siti Hanisah Ishak and Tuan Nor Fatanah Tuan Mohd Ariffin - Jaafar, Siti Azleah Hanim; Ishak, Siti Hanisah; Tuan Mohd Ariffin, Tuan Nor Fatanah (2010)
The primary purpose of this study is to measure the level of acceptance of Non Academic Staff in UiTM Jengka Pahang on national identity card (NIC) and driving license (OL) applications embedded in the Malaysia government multipurpose smartcard (called MyKad). A research framework is developed based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The method of this study is Quantitative and the research design is descriptive research which will be used to describe the level of user acceptance on MyKad application (NIC and OL). The sampling frame for this study will be based on the name list of Non Academic Staff across departments in UiTM Jengka Pahang. The stratified random sampling technique is chosen for this study because the populations represent a number of different departments. The survey instrument to be used is questionnaire and it will be distributed personally by hand to respondents.